PELATIHAN PENGGUNAAN APLIKASI PENDATAAN PENDUDUK PADA DISTRIK TANAH MIRING - Reza Zubaedah; Nasra Pratama Putra; Stanly H. D Loppies (Musamus Devotion Journal, 2021)
Tanah Miring District is a district in Merauke regency consisting of 2986 inhabitants and there are fourteen villages namely Yasa Mulya, Sumber Harapan, Waninggap Say, Waningap Miraf, Isano Mbias, New Life, Amunkay, Yaba Maru, Tambat Sarmayam Indah, Follow Bob, Soa, Bersehati, and Kamangi. At the District Office the manual data collection process so that errors often occur such as obstacles when searching for information about new residents, as well as residents who moved from the district. With the existence of KKN - TEMATIK UNMUS 2019 in the form of population data collection in the Tanah Miring District which is a technological development to facilitate population data collection so that the data collection process is no longer done manually. Constraints in the training district of using the application have not been implemented optimally so that the team of lecturers do the service by conducting training in the use of population data collection applications. Stages made by the team ie the trainees were given material about the application features and manuals and then the participants were given the opportunity to discuss the material that was given. Opportunities for questions and answers are given to clarify matters that are still in doubt. Participants practice to use the application. Participants are given further guidance to print reports. The results of the training are analyzed for further input and improvement. By conducting interviews with trainees as much as 80% of participants can understand the results of the training